Macro-Financial Aspects of Climate Change - Feyen, Erik; Utz, Robert; Zuccardi Huertas, Igor; Bogdan, Olena; Moon, Jisung (World Bank, Washington, DC, 2020)
This paper examines the interaction between macro-financial and climate-related risks. It brings together different strands of the literature on climate-related risks and how these relate to macro-financial management and risks. Physical impacts of climate change as well as the transition toward a resilient low-carbon economy pose significant challenges for macro-financial management, as they can damage the balance sheets of governments, households, firms, and financial institutions due to the adverse and possibly abrupt impacts on investment and economic growth, fiscal revenue and expenditure, debt sustainability, and the valuation of financial assets. In turn, macro-financial risks translate into weakened resilience to physical climate risks and constrained capacity for climate adaptation and mitigation efforts. The paper finds that many countries face the "double jeopardy" of simultaneous elevated climate-related and macro-financial risks. Reducing macro-financial risks in countries under double jeopardy is an important component of international efforts to tackle climate change to complement and support country-specific efforts.